Greywater Treatment Using Wetland (International Journal of Innovative Research in Engineering & Management, 2022)
Because of human and technical  improvements, the demand for freshwater has increased by  leaps and bounds globally in agricultural, industrial, and  home sectors, resulting in over-exploitation of freshwater  resources. The management of wastewater generated as a  by-product of these industries' different human activities is  a global challenge today. Greywater (GW) is a type of  wastewater produced in the domestic sector. Wetlands are  locations whereby water covers the soil or is present at or  near the soil's surface all year or for variable periods of  time throughout the year, including the growing season.  Water saturation (hydrology) influences how soil develops  as well as the sorts of biological communities that live in  and on the soil. Wetlands may provide habitat for both  marine and terrestrial organisms. The presence of water  over an extended period of time provides conditions that  encourage the growth of particularly adapted plants  (hydrophytes) and the creation of distinctive wetland  (hydric) soils. The water from the shower, sinks, and bathrooms is  commonly referred to as "grey water." With proper  treatment, greywater can be used for irrigation, allowing  residential and backyard gardens to reconnect to the  natural water cycle. "Root zone" is a technique that has  proven to be particularly effective in recycling greywater.  In this project artificial wetland has been constructed with  various layers of materials using root zone technique using  following plants Colocassia and canaindica. The greywater  was passed through the assembly which had been  constructed which consisted of settling tank, wetland unit,  filtration unit. The samples of grey water were taken.  COD, BOD, TDS, TSS were performed to find out these  properties. Then grey water was passed through the  assembly and these tests were conducted. The values show  us there is decrease in COD, BOD, TSS and TDS. This  decrease shows that the grey water can be for gardening  purpose in homes.
Keywords: COD; TSS; TDS; Grey Water